A comprehensive pancancer analysis reveals the potential value of RAR-related orphan receptor C (RORC) for cancer immunotherapy - He, Shengfu; Yu, Jiawen; Sun, Weijie; Sun, Yating; Tang, Mingyang; Meng, Bao; Liu, Yanyan; Li, Jiabin (Frontiers in Genetics, 2022)
Background: RAR-related Orphan Receptor C (RORC) plays an important role in autoimmune responses and inflammation. However, the function of RORC in cancer immunity is still unclear. The potential value of RORC in cancer immunotherapy needs to be further studied. Methods: The expression data and clinical information for 33 cancers were obtained from UCSC-Xena. The correlation between RORC expression and clinical parameters was analyzed using the limma software package to assess the prognostic value of RORC. Timer2.0 and DriverDBv3 were used to analyze the RORC mutational profile, as well as the RORC methylation profile. The relevant signaling pathways were analyzed by GSEA. The correlation between RORC and the tumor microenvironment was further assessed. Including the infiltration of lymphocyte subsets obtained by CIBERSORT and the correlation between RORC and immunomodulators in pancancer datasets obtained by the TISIDB. In addition, the correlation between RORC and three immunotherapy biomarkers (tumor mutational burden, microsatellite instability, and programmed death receptor ligand-1) was further explored. Furthermore, the immunotherapeutic cohorts included GSE67501 and GSE168204, as well as IMvigor210, were obtained from the Gene Expression Omnibus database, and derived from a previously published study. Results: RORC was differentially expressed in many tumor tissues and normal tissues (20/33). In a small number of cancers, RORC expression was correlated with age (7/33), sex (4/33), and tumor stage (9/33). Furthermore, RORC expression showed prognostic value in many cancers. Especially in KIRC, LGG, and MESO. The mutation rate of RORC in most cancer types was low, while RORC showed different methylation type in multiple cancers. RORC was associated with a variety of biological processes and signal transduction pathways in different cancers. Furthermore, RORC was strongly correlated with immune cell infiltration, immunomodulators, and immunotherapy biomarkers. However, no significant association was found between RORC and immunotherapy response in the three immunotherapy cohorts. Conclusions Our findings revealed a potential immunotherapeutic value of RORC for different cancers and provides preliminary evidence for the application of RORC in cancer immunotherapy.